No linealidad de la relación entre la estructura de capital y sus determinantes - Javier Sánchez Vidal (Colegio de Economistas de A Coru\~na, 2009)
– The aim of this study is to analyze whether the factors influencing debt change their effect depending on the company's debt level. This could be very useful for studying for example high-debt firms' determinants. We work with a panel data of 17,776 companies for the 2001-2006 period and through quantile regressions find that quantile analysis provides a more complete view over the debt determinants than standard OLS regression. Leverage gets influenced by a pecking order behaviour and companies suffer from information asymmetry problems. There is some evidence of bankruptcy costs but not of the tax benefit of debt.
Keywords: 330; regresión cuantílica; estructura de capital; teoría de la jerarquía; tradeoff